2011
DOI: 10.1016/j.jpainsymman.2010.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Studies Comparing Numerical Rating Scales, Verbal Rating Scales, and Visual Analogue Scales for Assessment of Pain Intensity in Adults: A Systematic Literature Review

Abstract: NRSs are applicable for unidimensional assessment of PI in most settings. Whether the variability in anchors and response options directly influences the numerical scores needs to be empirically tested. This will aid in the work toward a consensus-based, standardized measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
1,506
0
46

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,082 publications
(1,570 citation statements)
references
References 78 publications
18
1,506
0
46
Order By: Relevance
“…It is common to assess pain using visual analog scales (VAS) or numeric rating scales (NRS). Despite their differences in granularity, possible modes of collection, and presentation requirements, these instruments provide congruent results 23. Therefore, to facilitate implementation and align with current practices, the working group agreed to recommend assessment of joint pain via either VAS or NRS (11‐item version) using a 1‐week recall period 19, 20.…”
Section: Resultsmentioning
confidence: 99%
“…It is common to assess pain using visual analog scales (VAS) or numeric rating scales (NRS). Despite their differences in granularity, possible modes of collection, and presentation requirements, these instruments provide congruent results 23. Therefore, to facilitate implementation and align with current practices, the working group agreed to recommend assessment of joint pain via either VAS or NRS (11‐item version) using a 1‐week recall period 19, 20.…”
Section: Resultsmentioning
confidence: 99%
“…Viñuela-Fernández et al (2011) observed a higher repeatability when students scored horse laminitis on a VAS compared with two ordinal scales. Finally, in their comprehensive review of the literature comparing the available clinical tools for the self-reporting of pain in human patients, Hjermstad et al (2011) found that the most commonly used scales (i.e. a numerical rating scale with 11 categories, a verbal rating scale with 7 categories, and a 100-mm VAS) had comparable performances.…”
Section: Discussionmentioning
confidence: 99%
“…However, the aggregation of categories or their retrospective simplification has been recommended by some authors as one of the methods to increase inter-observer repeatability when assessing lameness in practical settings (Brenninkmeyer et al, 2007;Channon et al, 2009;D'Eath, 2012) and the use of few gait-scoring categories is indeed common in farm assurance schemes for pigs (Welfare Quality ® , 2009;RSPCA, 2012;BPEX, 2013). The number of scores available in any given scale is important because it determines the smallest degree of discrimination possible: scales with only two or three response levels offer limited opportunity to fully exploit the trained observer's discriminative capacities (Hjermstad et al, 2011). From an epidemiological and animal welfare perspective, the reduction of the number of gaitscoring categories, particularly when these are reduced to a simple 'lame/non-lame' classification, is likely to entail the loss of potentially important information on the lameness status of individual sows and of entire sow herds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, only individual reports can be found in the available literature in which the VAS (taken from the pain assessment methodology) has been used to assess anxiety in hospitalized patients awaiting surgery. 8 In the Polish literature, however, there is no study on the use of VAS to evaluate dental anxiety.…”
mentioning
confidence: 99%